Acclimation-induced changes in cell membrane composition and influence on cryotolerance of in vitro shoots of native plant species - Funnekotter, Bryn; Kaczmarczyk, Anja; Turner, S.; Bunn, E.; Zhou, W.; Smith, S.; Flematti, G.; Mancera, Ricardo (Springer, 2013)
Cell membranes are the primary sites of cryopreservation injury and measuring changes to membrane composition arising from cold acclimation may assist with providing a rationale for optimising cryopreservation methods. Shoot tips from two south-west Western Australian species, Grevillea scapigera and Loxocarya cinerea, and Arabidopsis thaliana (reference species) were subjected to cryopreservation using the droplet vitrification protocol. Two pre-conditioning regimes involving a constant temperature (23 °C, CT with a 12 h light/dark cycle) or an alternating temperature (AT) regime (20/10 °C with a 12 h light/dark cycle) were compared. Soluble sugars, sterols and phospholipids present in the shoot tips were analysed. Use of AT pre-conditioning (acclimation) resulted in a modest decrease in cryotolerance in A. thaliana, increased cryotolerance in G. scapigera, and increased survival in the non-frozen control explants of L. cinerea in comparison to CT pre-conditioning. Increased cryotolerance was accompanied by a higher total sugar sterol and phospholipid content, as well as an increase in strong hydrating phospholipid classes such as phosphatidylcholine. The double bond index of bound fatty acyl chains of phospholipids was greater after AT pre-conditioning, mostly due to a higher amount of monoenes in A. thaliana and trienes in G. scapigera and L. cinerea. These findings suggest that AT pre-conditioning treatments for in vitro plants can have a positive influence on cryotolerance for some plant species and this may be related to observed changes in the overall composition of cell membranes. However, alternative factors (e.g. oxidative stress) may be equally important with other species (e.g. L. cinerea).